RADIOCARBON DATING OF THE OLD ASH OF AITON, ROMANIA - PATRUT, Adrian; PATRUT, Roxana T.; RAKOSY, László; RAŢIU, Ileana-Andreea; LOWY, Daniel A.; BODIS, Jenö; REDEN, von, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The article reports the AMS (accelerator mass spectrometry) radiocarbon investigation results of the old common ash of Aiton. Five wood samples were collected from the trunk of the tree. The deepest ends of the samples were analysed by AMS radiocarbon. We found radiocarbon dates between 165 ± 20 BP and 240 ± 18 BP, which correspond to calibrated ages of 230 – 360 years. These results, combined with a ring counting estimate, indicate an age of 330 ± 30 years for the ash of Aiton. By this value, the ash of Aiton becomes the oldest known common ash with accurate dating results.